Somatosensorimotor and Odor Modification, Along with Serotonergic Processes Underlying the Social Deficits in BTBR T+ Itpr3tf/J and BALB/cJ Mouse Models of Autism. (1st October 2020) - Arakawa, Hiroyuki
Highlights: BALB/cJ mice exhibited social contact but not approach to volatile cues. BTBR mice failed to show social approach and contact. BALB/cJ mice have tactile impairment linked to their social strategy. BTBR mice release odor cues that induce avoidance in recipients. 5HT agonist rescued social approach in BTBR but not in BALB/cJ mice. Abstract: Autism is a complex spectrum of disorders characterized by core behavioral deficits in social communicative behavior, which are also required for comprehensive analysis of preclinical mouse models. As animal models of the core behavioral deficits in autism, two inbred mouse strains, BTBR T+ Itpr3 tf /J (BTBR) and BALB/cJ (BALB), were compared with the standard social strain, C57BL/6J (B6), regarding a variety of behavioral factors underlying social communicative interactions, including olfactory and tactile sensory processes, social recognition abilities and behavioral expression strategies. Although both female BTBR and BALB mice can express social recognition and approach behavior depending on the stimuli they encounter, the available sensory modalities, along with modulation of the serotonergic system, differ between the two strains. BALB mice have deficits in using volatile olfactory cues and tactile information in a social context; they fail to exhibit a social approach to volatile cues and seek nonvolatile cues by exhibiting substantial sniff/contact behavior when allowed direct contact with social opponents. Systemic injection of the serotonin (5-HT1A) agonist buspirone has little effect on these social deficits, suggesting a congenitally degraded serotonergic system in BALB mice. In contrast, BTBR mice exhibit impaired body coordination and social motivation-modified olfactory signals, which are relevant to a reduced social approach. A systemic injection of the 5-HT1A agonist restored these social deficits in BTBR mice, indicating that a downregulated serotonergic system is involved in the social deficits exhibited by BTBR mice.